Appendices dans le discours: aspects syntaxiques, prosodiques et pragmatiques - Apothéloz, Denis; Grobet, Anne (Travaux neuchâtelois de linguistique, 2005)
This paper presents an overview of syntactic, prosodic and functional (i.e. pragmatic) properties of right dislocations (defined here as appendixes) in French. Firstly, it addresses the problem of the definition of these constructions and of their classification. The authors also address the question of the grammaticalization of these constructions. They argue that this question is highly important in the analysis of the pragmatic functions of appendixes. In this discussion, a distinction is made between construction and configuration. In the second part of the article, the various pragmatic functions of appendixes are examined. Two related hypotheses are presented, which are assumed to explain many appendixes. The first one concerns informational flow; the second one concerns prosodic properties of discourse, especially in conversation. These hypotheses make it possible to account for many semantic, pragmatic, and interactional «effects» of appendixes.